Gaya Bahasa Figuratif dalam Syair Ana Ma’a Al –Irhab (Aku Bersama Terorisme) karya Niizar Taufik Qabbani - Ulpa Rizki Amanda; Muhammad Walidin (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to describe terrorism through figurative language styles, both comparisons and linkages. This studyuses a stylistic approach that focuses its study on forms of linguistic formation, especially those contained in literarytexts. Stylistics is intended to explain the function of beauty in the use of certain linguistic forms, from aspects of sound, structure, lexical, figurative language, rhetorical means, to graphology. Based on the results of the above research on the poem ? ??????? by Nizar Taufik Qabbani, it was found that the types of figurative language styles in the lines of the poem, among others, are simile ( ?? ? ? ? ?? ), metaphor (???? ? ? ??? ), allegory ( ?? ? ?? ?? ), metonymy ( ? ??? ? ?? ). ), and synecdoche ( ?? ?? ?? ) in the type of pars pro toto and in the type of totum properte, but dominates in the description of the term terrorism in this poem.